2003
DOI: 10.1126/science.1084114
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Plant and Animal Genetic Records from Holocene and Pleistocene Sediments

Abstract: Genetic analyses of permafrost and temperate sediments reveal that plant and animal DNA may be preserved for long periods, even in the absence of obvious macrofossils. In Siberia, five permafrost cores ranging from 400,000 to 10,000 years old contained at least 19 different plant taxa, including the oldest authenticated ancient DNA sequences known, and megafaunal sequences including mammoth, bison, and horse. The genetic data record a number of dramatic changes in the taxonomic diversity and composition of Ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
478
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 559 publications
(491 citation statements)
references
References 19 publications
8
478
0
5
Order By: Relevance
“…Short DNA sequences can persist for long time periods mainly in cold environments with reduced exposure or absence of light (Willerslev et al 2003). This has been observed in studies conducted in old sediments and ice cores (Hofreiter, Mead, Martin, & Poinar, 2003;Willerslev, Capellini, Boomsman, & Nielsen, 2007).…”
Section: Trophic Interactions and Dietary Studiesmentioning
confidence: 83%
“…Short DNA sequences can persist for long time periods mainly in cold environments with reduced exposure or absence of light (Willerslev et al 2003). This has been observed in studies conducted in old sediments and ice cores (Hofreiter, Mead, Martin, & Poinar, 2003;Willerslev, Capellini, Boomsman, & Nielsen, 2007).…”
Section: Trophic Interactions and Dietary Studiesmentioning
confidence: 83%
“…The problem is compounded by the fact that calibration rates are ultimately based on a known fossil record (Doolittle, 1997;Doolittle et al, 1996;Feng et al, 1997;Lee, 1999), and even then rates may vary between lineages (Ochman et al, 1999;Soltis et al, 2002). In addition, there are no reliable reports of 'molecular fossils' that are more than 50-100 million years old (Poinar et al, 1996;Willerslev et al, 2003). Such problems have been highlighted by Sneath (1974) and are beginning to be discussed again.…”
Section: Genome Of R Balticamentioning
confidence: 99%
“…Soils and sediments often contain DNA that can be amplified by PCR (Hofreiter et al 2003;Willerslev et al 2003) and bacterial DNA sequences have been found in sediments that go back over half a million years (Willerslev et al 2004). Therefore, there is the possibility that DNA bound to minerals (Cleaves et al 2010;Lyon et al 2010) could exist on the Martian surface (Fajardo-Cavazos et al 2010) and be accessible for analysis.…”
Section: Introductionmentioning
confidence: 99%